Coping behavior of convicts: towards the potential of social identity theory - Melnikova, D.V.; Bovina, I.B.; Debolsky, M.G. (Psihologiâ i pravo, 2025)
The focus of our attention in this paper is to discuss the coping behavior of inmates and to consider the potential of applying social identity theory to understanding this phenomenon. Coping behavior is a multidimensional phenomenon that can be defined as conscious behavior aimed at active interaction with a stressful or difficult life situation, i.e. changing it (when it is controllable) or adapting to it (when the situation is uncontrollable). Under social identity we understand an individual's knowledge of his/her belonging to certain social groups together with some emotional and value significance of this group membership for him/her. Having considered the main foreign and domestic approaches to understanding the coping behavior, as well as some provisions of the theory of social identity, we can make a key conclusion that it is important to consider the coping behavior of convicts not only at the individual, but also at the social level. The main thesis discussed in the framework of this theoretical and analytical work is the idea that the content of coping behaviors in a difficult life situation is, among other things, determined by the orientation of social groups in which a person is included. Due to the fact that such groups can have antisocial orientation, the study of the characteristics of a person's social identities and the degree of identification with this or that group becomes especially relevant, since, being a member of a social group, a person's coping behavior in a difficult life situation is determined by the orientation of social groups. В фокусе нашего внимания в настоящей работе находится обсуждение совладающего поведения осужденных и рассмотрение потенциала применения положений теории социальной идентичности к пониманию данного феномена. Совладающее поведение - многомерный феномен, который можно определить как осознанное поведение, направленное на активное взаимодействие со стрессовой или трудной жизненной ситуацией, то есть ее изменение (когда она поддается контролю) или приспособление к ней (в случае, когда ситуация не поддается контролю). Под социальной идентичностью мы понимаем знание индивидом своей принадлежности к определенным социальным группам вместе с некоторой эмоциональной и ценностной значимостью для него этого группового членства. Рассмотрев основные зарубежные и отечественные подходы к пониманию совладающего поведения, а также некоторые положения теории социальной идентичности, можно сделать ключевой вывод о том, что важно рассмотреть совладающее поведение осужденных не только на индивидуальном, но и на социальном уровне. Главным тезисом, обсуждаемым в рамках данной теоретико-аналитической работы, является идея о том, что содержание копингов в трудной жизненной ситуации, в том числе, определяется направленностью социальных групп, в которые включен человек. В связи с тем, такие группы могут иметь антисоциальную направленность. Особенно актуальным становится исследование характеристик социальных идентичностей человека и степени идентификации с той или иной группой, поскольку, в логике подхода социальной идентичности, поведение человека, являющегося членом группы с антисоциальной (криминальной) направленностью, устойчиво регулируется нормами такой группы.